Determinants Of Coffee Shop Business Income In Denpasar City - Ida Bagus Gede Wisnu Ari Susetya; Anak Agung Istri Ngurah Marhaeni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The number of coffee shops that appear in Denpasar City makes business competition in this city increasing. The increasing number of coffee shops makes the current market competition also increases, so it is important for coffee shop owners to pay attention to their business income factors so that business continuity is maintained. The purpose of this study is to analyze how; 1) The simultaneous effect of e-commerce utilization, working hours, technology, and capital on coffee shop income; 2) The partial effect of e-commerce utilization, working hours, technology, and capital on coffee shop income; 3) The role of capital in moderating the influence of technology on coffee shop income in Denpasar City. This study used a quantitative approach with associative explanation level. Data type that used was primary data with a population of 151 coffee shop businesses in Denpasar City. The sample in this study was 61 coffee shop businesses collected through observation, interview, and in-depth interview methods. The sample was selected through probability sampling technique with a simple random sampling approach. Data analysis technique methods used in this study include descriptive statistics, classical assumption test, and moderated regression analysis. The results of the analysis show that; 1) E-commerce utilization, working hours, technology, and capital has a significant simultaneous effect on income; 2) E-commerce utilization, technology, and capital has a partially significant positive effect on income, but working hours do not have a significant effect on income; 3) Capital variables do not moderate the influence of technology on coffee shop income in Denpasar City. Based on the results of the research, it is expected that the relevant government will routinely hold skills training programs and capital loans for recorded coffee shop business owners so that the sustainability of the coffee shop business in Denpasar City is maintained and developed.